Chronicle of a Decline Foretold : Has China Reached the Lewis Turning Point? - Das, Mitali; N'Diaye, Papa. (Washington, D.C. : International Monetary Fund, 2013)
China is on the eve of a demographic shift that will have profound consequences on its economic and social landscape. Within a few years the working age population will reach a historical peak, and then begin a precipitous decline. This fact, along with anecdotes of rapidly rising migrant wages and episodic labor shortages, has raised questions about whether China is poised to cross the Lewis Turning Point, a point at which it would move from a vast supply of low-cost workers to a labor shortage economy. Crossing this threshold will have far-reaching implications for both China and the rest of the world. This paper empirically assesses when the transition to a labor shortage economy is likely to occur. Our central result is that on current trends, the Lewis Turning Point will emerge between 2020 and 2025. Alternative scenarios-with higher fertility, greater labor participation rates, financial reform or higher productivity-may peripherally delay or accelerate the onset of the turning point, but demographics will be the dominant force driving the depletion of surplus labor.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet